2021
DOI: 10.1111/jerd.12791
|View full text |Cite
|
Sign up to set email alerts
|

Experimental methodologies to evaluate the masking ability of dental materials: A systematic review

Abstract: Objective: To conduct a systematic review on the masking ability of discolored substrates, analyzing the capacity and quality of the response produced by the different methodologies and techniques applied to overcome this clinical challenge. Materials and methods:The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The electronic search was conducted in MEDLINE/PubMed, Scopus and Web of Science databases, without date restriction. In vitro studies, writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Limited studies have assessed the clinical influence of dental ceramic thicknesses and composition on the masking ability and translucency of definitive prosthetic restorations [19,20]. Moreover, maintaining a proper balance between translucency and ceramic thickness is crucial especially in cases of dark discoloration of the underlying tooth structure or amalgam restorations [21]. Furthermore, thin ceramic restorations as dental veneers are favorable for several patients that seek high esthetic smile demand; however, their color properties are still sparse [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have assessed the clinical influence of dental ceramic thicknesses and composition on the masking ability and translucency of definitive prosthetic restorations [19,20]. Moreover, maintaining a proper balance between translucency and ceramic thickness is crucial especially in cases of dark discoloration of the underlying tooth structure or amalgam restorations [21]. Furthermore, thin ceramic restorations as dental veneers are favorable for several patients that seek high esthetic smile demand; however, their color properties are still sparse [22,23].…”
Section: Introductionmentioning
confidence: 99%
“… 68 , 69 Another way to evaluate the aesthetic aspect is by the masking ability of the dental material, which can be defined as the color difference result (ΔE) between the core and the coating. 70 When this value equals zero, the background color is hidden by the outlying structure. A parameter that influences the masking ability is opalescence, which is one of the optical properties that displays the blueness of the reflected light spectrum and brownness-orangeness of the transmitted light spectrum.…”
Section: All Ceramicmentioning
confidence: 99%
“…R T (rotation function) accounts for the interaction between chroma and hue differences in the blue terms for the conditions and illuminating influence. 9,16 In the present study, parametric factors were all set to 1 (…”
Section: Color Measurementmentioning
confidence: 99%
“…[6][7][8]15 The masking ability of resin composites has been currently evaluated by using the translucency parameter (TP), contrast ratio (CR), or application of color difference (ΔE) formulas. [16][17][18][19] A recent study 16 has shown that CIELAB and CIEDE2000 metrics associated with the perceptibility and acceptability thresholds are the most appropriate methodology for evaluating masking ability. Also, according to recent recommendations, International Commission on Illumination (CIE), 20 the CIEDE2000 metric should be used for color differences computation.…”
mentioning
confidence: 99%